Aqui você faz notícia?: uma análise de jornalismo cidadão nas páginas do Eu-Repórter - Nascimento, Adriana Silva do (2011)
Featuring a historic showing the configuration of journalism as a professional activity and business, this study develops a discussion about the journalistic open to participation from individuals with no formation as a journalist to reach at a model of citizen journalism in which news are guided by the public interest and contribute to the strengthening of public visibility and access to information that promotes deliberation. Through analysis of the news site Eu-Repórter, it is observed that the exercise of citizen journalism model is not viable in a movement within a vehicle for communication of traditional media, as news goes through filters constructed by a market logic that foresees economic and political interests outside the media's role as a space for public debate broadened.